2013
DOI: 10.4236/jbnb.2013.43a004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gabaergic Phenols on Phospholipid Bilayers as Evaluated by <sup>1</sup>H-NMR

Abstract: The phenols propofol and thymol, and lately carvacrol, eugenol and chlorothymol, have been shown to act as positive allosteric modulators on GABA A receptor, which is the main inhibitory receptor of the central nervous system. GABA A receptor is an intrinsic membrane protein which activity may be affected by surface-active compounds and by physical changes in the membrane. Recently, we demonstrated that these phenols interacted with the lipid membrane phase, suggesting their anesthetic activity could be the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The authors reported the localization of these phenols in the region between the polar groups (choline molecule), the glycerol backbone and the first atoms of the acyl chains. This localization reduced the repulsive forces among the phospholipid head groups, thus decreasing the mobility of the hydrocarbon chains, as revealed by 1 H spin relaxation times (Reiner et al, 2013). So, Eug may not diffuse from the lipid bilayer to the surrounding aqueous phase (Fujisawa et al, 1988); this may explain the increase in the vesicle size (Tables 1 and 2).…”
Section: Effects Of Ceo and Eug On The Mean Size Pdi And Zeta Potentmentioning
confidence: 96%
See 1 more Smart Citation
“…The authors reported the localization of these phenols in the region between the polar groups (choline molecule), the glycerol backbone and the first atoms of the acyl chains. This localization reduced the repulsive forces among the phospholipid head groups, thus decreasing the mobility of the hydrocarbon chains, as revealed by 1 H spin relaxation times (Reiner et al, 2013). So, Eug may not diffuse from the lipid bilayer to the surrounding aqueous phase (Fujisawa et al, 1988); this may explain the increase in the vesicle size (Tables 1 and 2).…”
Section: Effects Of Ceo and Eug On The Mean Size Pdi And Zeta Potentmentioning
confidence: 96%
“…Although the effect of eugenol on lipid bilayer properties has previously been studied (Fujisawa, Kadoma, & Komoda, 1988;Manabe, Nakayama, & Sakamoto, 1987;Pandey, Lathika, & Mishra, 2006;Reiner, Fraceto, De Paula, Perillo, & Garcia, 2013), our study is the first to deal with the encapsulation of eugenol and CEO in lipid vesicles. Besides, the effect of phospholipid type on the vesicle characteristics is also studied.…”
Section: Introductionmentioning
confidence: 99%
“…The location of the drug in the lipid membrane is an important issue, being discussed in the literature for liposomes. Reiner et al [26] suggested that eugenol is able to insert in egg phosphatidylcholines, being located in the region between the polar groups, with the glycerol and first atoms of the acyl chain. This can reduce the repulsive forces among the lipid head groups, permitting closer molecular packing and decreasing the mobility of hydrocarbon chains, as revealed by 1 H-NMR.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane fluidity, curvature, elasticity and dipolar arrangement modulate the receptor-mediated interactions between drugs and membranes [31]. The anesthetic effects of alkylphenols are referred to as the combined results of their interactions with receptor or channel proteins and those with membrane lipids to modify the lipid environments surrounding such functional proteins [32].…”
Section: Discussionmentioning
confidence: 99%